Innovations Towards Sustainability Conditions and Consequences - Lehmann-Waffenschmidt, Marco.; Lehmann-Waffenschmidt, Marco. (Sustainability and Innovation, 2007)
The volume contains eight articles together with comments by twenty authors and discussants on the topic of innovations and sustainability. It provides a competently written, balanced and differentiated state-of-the-art insight into the relation between innovations and sustainability from the perspective of evolutionary economics. The scope of the contributions encompasses the technological, social, organizational, and political dimensions of the topic. Each article is discussed by a competently written commentary providing a critical evaluation and relating it to the relevant literature. Particular interest lies on the issues of steering opportunities and path formation capabilities by decentralized agents, or governmental institutions from the viewpoint of evolutionary economics.